2017
DOI: 10.1017/s1478951517000013
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of treatment of chronic disease: Validity and reliability of the Turkish version of the Spiritual Well-Being Scale

Abstract: Our study determined that the Turkish version of the FACIT-Sp has validity and reliability and can be used in Turkish society. We believe that the scale can be used safely in determining convenient care and in planning individual educational programs to enhance patients' spiritual well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…19 A study of the validity and reliability of the Turkish version of the FACIT-Sp was conducted by Aktürk et al: the Cronbach's alpha for the FACIT-Sp was 0.87, meaning the sub-scale had a Cronbach's alpha of 0.78, the peace sub-dimension had a Cronbach's alpha of 0.81, and the belief sub-dimension had a Cronbach's alpha of 0.93. 20 In the present study, Cronbach's alpha was determined to be 0.88 for the FACIT-Sp, 0.80 for the meaning subscale, 0.81 for the peace subscale, and 0.95 for the faith subscale.…”
Section: The Facit Spiritual Well-being Scale (Facit-sp)mentioning
confidence: 62%
“…19 A study of the validity and reliability of the Turkish version of the FACIT-Sp was conducted by Aktürk et al: the Cronbach's alpha for the FACIT-Sp was 0.87, meaning the sub-scale had a Cronbach's alpha of 0.78, the peace sub-dimension had a Cronbach's alpha of 0.81, and the belief sub-dimension had a Cronbach's alpha of 0.93. 20 In the present study, Cronbach's alpha was determined to be 0.88 for the FACIT-Sp, 0.80 for the meaning subscale, 0.81 for the peace subscale, and 0.95 for the faith subscale.…”
Section: The Facit Spiritual Well-being Scale (Facit-sp)mentioning
confidence: 62%
“…Higher scores indicate greater spiritual well‐being. Cronbach's alpha coefficient was 0.87, and a total item correlation for each item ranged between 0.62 and 0.93 in the Turkish validity and reliability study (Aktürk, Erci, & Araz, 2017).…”
Section: Methodsmentioning
confidence: 97%
“…The range of total score changes from 0 to 48, with lower scores show lower SWB. [31] The validity and reliability for Turkish version was studied by Aktürk et al [32] (2017), who reported a Cronbach's alpha value of 0.87. The Cronbach's alpha value was found to be 0.77 for patients with HF and 0.86 for family caregivers in the present study.…”
Section: The Depression Anxiety Stress Scale (Dass)mentioning
confidence: 99%